2023
DOI: 10.1177/25152459231202724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Pedagogical Effectiveness of Study Preregistration in the Undergraduate Dissertation

Madeleine Pownall,
Charlotte R. Pennington,
Emma Norris
et al.

Abstract: Research shows that questionable research practices (QRPs) are present in undergraduate final-year dissertation projects. One entry-level Open Science practice proposed to mitigate QRPs is “study preregistration,” through which researchers outline their research questions, design, method, and analysis plans before data collection and/or analysis. In this study, we aimed to empirically test the effectiveness of preregistration as a pedagogic tool in undergraduate dissertations using a quasi-experimental design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
0
0
0
Order By: Relevance
“…The replication "crisis" and credibility revolution have shown that published studies in psychology are underpowered (Korbmacher et al, 2023;Open Science Collaboration, 2015;Vazire, 2018). Pre-registration of a study involves outlining the study and hypotheses before data collection begins (Chambers et al, 2014;Nosek & Lakens, 2014;Stewart et al, 2020), and details of a power analyses or limitations on resources are often used to provide justification for the pre-registered sample quota (Pownall et al, 2023;van den Akker, Assen, et al, 2023;van den Akker, Bakker, et al, 2023). Given the combined issues of publish-or-perish and that most non-significant results do not result in published manuscripts, power analysis may be especially critical for early career researchers to increase the likelihood that they will identify significant effects if they exist (Rosenthal, 1979;Simmons et al, 2011).…”
Section: Planning With Multiple Stimulimentioning
confidence: 99%
“…The replication "crisis" and credibility revolution have shown that published studies in psychology are underpowered (Korbmacher et al, 2023;Open Science Collaboration, 2015;Vazire, 2018). Pre-registration of a study involves outlining the study and hypotheses before data collection begins (Chambers et al, 2014;Nosek & Lakens, 2014;Stewart et al, 2020), and details of a power analyses or limitations on resources are often used to provide justification for the pre-registered sample quota (Pownall et al, 2023;van den Akker, Assen, et al, 2023;van den Akker, Bakker, et al, 2023). Given the combined issues of publish-or-perish and that most non-significant results do not result in published manuscripts, power analysis may be especially critical for early career researchers to increase the likelihood that they will identify significant effects if they exist (Rosenthal, 1979;Simmons et al, 2011).…”
Section: Planning With Multiple Stimulimentioning
confidence: 99%